Regiochemistry of Donor Dendrons Controls the Performance of Thermally Activated Delayed Fluorescence Dendrimer Emitters for High Efficiency Solution‐Processed Organic Light‐Emitting Diodes (Adv. Sci. 20/2022). Issue 20 (15th July 2022) - Sun, Dianming; Saxena, Rishabh; Fan, Xiaochun; Athanasopoulos, Stavros; Duda, Eimantas; Zhang, Ming; Bagnich, Sergey; Zhang, Xiaohong; Zysman‐Colman, Eli; Köhler, Anna
Abstract : Thermally Activated Delayed Fluorescence Dendrimers In article number 2201470, Dianming Sun, Xiaohong Zhang, Eli Zysman‐Colman, Anna Köhler, and co‐workers develop a series of thermally activated delayed fluorescence dendrimers with a deep understanding of the structure–property relationship. The study reveals that the reorganization energies, and thus the reverse intersystem crossing rate can be controlled by the regiochemistry of the donor dendrons. They demonstrate a two‐fold improved, external quantum efficiency in solutionprocessed organic light‐emitting diodes.